Analysis of The Influence of Digital Integrated Employee System on Employee Performance in Banking Industry - Usmia, Sitti; Anwar LC, Mohammad; Wulandari; Wildan Nuryanto, Uli; Malini Lubis, Fatimah (Jurnal Informasi dan Teknologi, 2024)
This research aims to determine the benefits of the barcode system in private banks. Researchers employ a quantitative approach, which is a form of survey research. The research design uses a descriptive analysis method. To collect data, the author conducted interviews, distributed questionnaires and observations, and tracked documents related to the barcode system in the bank. The population in this study were employees of the Operation Division. This research employed the non-probability sampling technique. Researchers used SPSS. By using a barcode system, employees gain several significant benefits. First, the barcode system makes it easier to maintain IT equipment at the bank by providing accurate information about the status and location of the devices, as well as creating a greater sense of responsibility for the devices used. Apart from that, using barcodes also helps overcome the problem of data redundancy, maintain data security, speed up the process of calculating asset depreciation, and speed up the decision-making process. Implementing the barcode system also makes it easier and faster to process asset stock-taking using the asset inventory application, thereby increasing overall work productivity. However, the test results show that using the barcode system is not practical in improving the performance of employees. The calculated t value reveals no significant difference in performance before and after the barcode system implementation.